Benign melanocytic naevi as a risk factor for malignant melanoma. Issue 6535 (14th June 1986) - Swerdlow, A J; English, J; MacKie, R M; O'Doherty, C J; Hunter, J A; Clark, J; Hole, D J
Abstract : Examination of 180 patients with cutaneous malignant melanoma and 197 control patients in a case-control study showed that the risk of melanoma is strongly related to numbers of benign melanocytic naevi (moles). Some unusual features of naevi--a diameter exceeding 7 mm, colour variation, and irregular lateral outline--also showed a strong association with the risk of melanoma, but the relation of numbers of naevi to risk was present even in the group of patients whose naevi had none of these unusual features. Biopsy of clinically atypical naevi from several of the patients at highest risk generally did not show dysplastic histology. Thus a group of people at high risk of melanoma may be identified by using simple clinical assessment of naevi.